A Novel Mutation in the Mitochondrial DNA Cytochrome b Gene (MTCYB) in a Patient With Mitochondrial Encephalomyopathy, Lactic Acidosis, and Strokelike Episodes Syndrome. (February 2013) - Emmanuele, Valentina; Sotiriou, Evangelia; Rios, Purificación Gutierrez; Ganesh, Jaya; Ichord, Rebecca; Foley, A. Reghan; Akman, H. Orhan; DiMauro, Salvatore
Mutations in the mitochondrial DNA cytochrome b gene ( MTCYB ) have been commonly associated with isolated mitochondrial myopathy and exercise intolerance, rarely with multisystem disorders, and only once with a parkinsonism/mitochondrial encephalomyopathy, lactic acidosis, and strokelike episodes (MELAS) overlap syndrome. Here, we describe a novel mutation (m.14864 T>C) in MTCYB in a 15-year-old girl with a clinical history of migraines, epilepsy, sensorimotor neuropathy, and strokelike episodes, a clinical picture reminiscent of MELAS. The mutation, which changes a highly conserved cysteine to arginine at amino acid position 40 of cytochrome b, was heteroplasmic in muscle, blood, fibroblasts, and urinary sediment from the patient but absent in accessible tissues from her asymptomatic mother. This case demonstrates that MTCYB must be included in the already long list of mitochondrial DNA genes that have been associated with the MELAS phenotype.